Reading attitudes of UiTM Penang students : An exploratory study / Leele Susana Jamian and Emily Jothee Mathai - Jamian, Leele Susana; Jothee Mathai, Emily (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
Reading is a vital behavioural factor in a knowledge-based society. Positive reading attitudes particularly in English would lead to a higher level of proficiency. A study by Gan Say Eng (2000) revealed that students with poor reading habits and attitudes reflect low levels of proficiency in the language. Within this context, a study on reading attitudes in English was conducted among 250 students at UiTM, Penang Branch pursuing BEL250, which is a proficiency course. The objective of the study was to examine students' perception of their reading attitudes. The study revealed that these students were aware of the importance of good reading attitudes. However, results also indicated that reading in English is not a priority among the students. Their reading attitudes in English remain largely intensive. They perceived reading in English as important but somehow they lack time due to their busy schedule related to their studies. It is hoped that the findings on students' reading attitudes would provide significant information where English proficiency is concerned